ON THE ASSESSMENT OF THE QUALITY OF BACHELOR'S THESIS - S. V. Stepanova (Высшее образование в России)
The fight against plagiarism in educational organizations has has acquired a superfluous character. The originality level of a text has been chosen as a quality indicator of bachelor's thesis, while the completeness, logic and literacy of the exposition were relegated to a secondary position. In many cases, this is unreasonable, especially when it comes to specialties in which unambiguous language and citations of legislative and regulatory acts are required. Most of graduates' efforts are aimed at finding various linguistic methods that increase the uniqueness level of the paper. And this affects knowledge. Practical work also requires specialists who are ready to execute the already developed standards and not to interpret them. Thus, we need a change in the quality assessment approach to scientific papers. The article outlines the main provisions and proposals for the introduction of new approaches.